The burden is great and the money little: Changing chronic disease management in low- and middle-income countries - Daniel D. Reidpath; Pascale Allotey (Edinburgh University Global Health Society, 2012)
Many health conditions are chronic, and only some of those chronic health conditions are NCDs. If the interest is on cause and prevention, then NCDs should be treated separately from other chronic diseases. If the interest is on health systems and management, then NCDs should be joined with other chronic diseases.